ESTEREOTIPOS POR SEXO EN LA TOMA DE DECISIONES PARA ELEGIR UNA CARRERA DE LA UNIDAD EDUCATIVA AMELIA GALLEGOS DÍAZ” PERIODO ABRIL -AGOSTO 2019 - Sisa León, Walter Iván (2020)
The purpose of this research project was to determine the relationship of stereotypes by sex in decision making, in the students of the third year of the Unified General Baccalaureate, parallel "A" for the election of a professional career in the Educational Unit " Amelia Gallegos Díaz ”, Riobamba, April-August 2019 period; the research variables that are stereotypes by sex that are determined as ideas or beliefs that are attributed to a person for this condition, and decision-making affected as a decision to act in any situation that presents several options or alternatives suggested.Methodologically, it has a quantitative approach; its design is non-experimental and correlational type.For the time of study it is transversal and for the basic and field objectives. population investigated were the students of the third year of the Unified General Baccalaureate, and their sample was the students of the parallel “A.” Two techniques were identified: the survey with its instrument, the questionnaire and a psychometric exam with its skills questionnaire. To conclude with the analysis of results, concluding that stereotypes have a significant influence on the ability to choose, and at the same time a negative convenience develops, which harms the decision making of an individual.